2013
DOI: 10.1371/journal.pone.0076146
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Oxidative Stress Are Elevated in the Brain, Blood, and Adrenal Glands during the Progression of Post-Traumatic Stress Disorder in a Predator Exposure Animal Model

Abstract: This study sought to analyze specific pathophysiological mechanisms involved in the progression of post-traumatic stress disorder (PTSD) by utilizing an animal model. To examine PTSD pathophysiology, we measured damaging reactive oxygen species and inflammatory cytokines to determine if oxidative stress and inflammation in the brain, adrenal glands, and systemic circulation were upregulated in response to constant stress. Pre-clinical PTSD was induced in naïve, male Sprague-Dawley rats via a predator exposure/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 48 publications
11
127
3
Order By: Relevance
“…This has been hypothesized to be the case in PTSD, where a study measuring levels of inflammatory cytokines and markers of OS suggests that inflammatory cytokines induce ROS production, which then amplifies the inflammatory response (169).…”
Section: Brain-body Interactions Of Stress Os and Inflammationmentioning
confidence: 99%
“…This has been hypothesized to be the case in PTSD, where a study measuring levels of inflammatory cytokines and markers of OS suggests that inflammatory cytokines induce ROS production, which then amplifies the inflammatory response (169).…”
Section: Brain-body Interactions Of Stress Os and Inflammationmentioning
confidence: 99%
“…The mechanisms by which peripheral inflammation may influence the central nervous system are still unclear, as reviewed by Andrews and Neises (2012). Cytokines are produced in the periphery, mainly by immune cells, and can cross the blood brain barrier (BBB) via passive and active transport mechanisms (Schiepers et al, 2005) and once in the brain, can activate microglia (Wilson et al, 2013). In one animal study, it was shown that lymphocytes may infiltrate the BBB following psychological stress (Lewitus et al, 2008), thus linking stress-related peripheral inflammation to signs of neuroinflammation and possibly behavioral changes.…”
Section: Mechanismsmentioning
confidence: 99%
“…Few clinical studies have been able to investigate this but in support of a primarily central process, Baker et al (2001) found that combat veterans with PTSD display higher levels of IL-6 in CSF, but not in plasma, compared to controls. Moreover, a recent animal model of PTSD found that inflammation in the brain was associated with PTSD, and that disease progression was also associated with increased oxidative stress in the brain as well as in the periphery (Wilson et al, 2013). However, another animal model of traumatic brain injury (TBI) and PTSD found that the presence of behaviors suggestive of PTSD did not exacerbate neuroinflammation associated with TBI (Acosta et al, 2013), speaking against a robust linkage between neuroinflammation and PTSD.…”
Section: Mechanismsmentioning
confidence: 99%
“…[57][58][59] In short, activated neuroinflammation is implicated in inhibited neurogenesis and synaptic plasticity (cognitive deficits) leading to the development and persistence of the behavioral manifestations of PTSD. Whereas, somatic inflammation seems to be directly involved in tissue damage, triggering and maintaining somatic comorbid pathologies.…”
Section: Discussionmentioning
confidence: 99%